If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a * 3a = 0 Reorder the terms for easier multiplication: 4 * 3a * a = 0 Multiply 4 * 3 12a * a = 0 Multiply a * a 12a2 = 0 Solving 12a2 = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '12'. a2 = 0 Simplifying a2 = 0 Take the square root of each side: a = {0}
| ln(6x+2)=ln(3x-19) | | -4.3-3z-2.9-z=-3z+5.7 | | -8m-8n+p-2=-10n-9p+8 | | 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= | | 5w^2+39w+5y=0 | | 9a+19=100 | | X^2-2x+528=0 | | 98=-2(-8x+8) | | 8cos^2x-4cosx-2=0 | | 6g=6g+-34 | | 3x+x+7=6x-2x+7 | | 0.25d+6=11 | | =5x | | N-3.5=6.5 | | 9f+15=15 | | (xy^2+y)dx+(x^2y-x)dy=0 | | 3+x/2=10 | | 8=4(b-2)+4 | | 32=-5x-8 | | 12(2p+11)=12(2p+12) | | 4x+12x-7=4(4x+9) | | -1=-2y+7 | | -15=9-8x | | 8=(b-2)+4 | | 5-6(2+6)=b-14 | | 4.75m+15=2.75m+6 |